The Complete Chloroplast Genome of Melocanna baccifera (Poaceae: Bambusoideae) and its Phylogenetic Implications - Thu-Thao Thi Huynh; Nga Thi Nguyen; Phi Anh Ngoc Nguyen; Anh-Duy Hoang Nguyen; Minh Trong Quang (HAYATI Journal of Biosciences, 2026)
Melocanna baccifera is a morphologically distinctive bamboo species in the subfamily Bambusoideae (Poaceae), recognized by a combination of diagnostic vegetative and reproductive characteristics, yet its chloroplast (cp) genomic features and phylogenetic position remain poorly understood. This study aimed to sequence, assemble, and annotate the complete cp genome of M. baccifera and to evaluate its phylogenetic implications within Bambusoideae. The complete cp genome of M. baccifera was de novo assembled into a 139,345 bp circular molecule with a typical quadripartite structure and a GC content of 38.9%. It comprised a large single-copy region of 82,927 bp, a small single-copy region of 12,768 bp, and a pair of inverted repeat regions of 21,825 bp each. The genome encoded a total of 129 genes, including 83 protein-coding genes, 38 transfer RNA genes, and eight ribosomal RNA genes. Comparative analysis showed that the cp genome of M. baccifera was similar to those of other Bambusoideae species in genome size, nucleotide composition, and gene content. Phylogenetic analysis placed M. baccifera in a well-supported clade with Schizostachyum species, consistent with currently recognized relationships within Bambusoideae. These findings provide a valuable plastid genomic resource for M. baccifera and improve our understanding of its evolutionary relationships, thereby offering a molecular foundation for future phylogenomic and evolutionary studies of bamboos.